2000
DOI: 10.1302/0301-620x.82b5.0820629
|View full text |Cite
|
Sign up to set email alerts
|

Does ‘Canal Clearance’ Affect Neurological Outcome After Thoracolumbar Burst Fractures?

Abstract: Surgical decompression of the spinal canal is presently accepted worldwide as the method of treatment for thoracolumbar burst fractures with neurological deficit in the belief that neurological recovery may be produced or enhanced. Our clinical and laboratory experience, however, indicates that the paralysis occurs at the moment of injury and is not related to the position of the fragments of the fracture on subsequent imaging. Since the preoperative geometry of the fracture may be of no relevance, our hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 34 publications
4
42
0
5
Order By: Relevance
“…Another interesting finding was that the outcome of overall decompressed patients, combining together data of early and late treatment, namely overlooking the time factor, was similar to that of conservatively managed patients. This agree with the observations of other authors, 32,[50][51][52][53] and suggest that timing may play a role in surgical decompression.…”
Section: Literature Reviewsupporting
confidence: 93%
See 2 more Smart Citations
“…Another interesting finding was that the outcome of overall decompressed patients, combining together data of early and late treatment, namely overlooking the time factor, was similar to that of conservatively managed patients. This agree with the observations of other authors, 32,[50][51][52][53] and suggest that timing may play a role in surgical decompression.…”
Section: Literature Reviewsupporting
confidence: 93%
“…Their results demonstrated that surgery does not offer a significant advantage compared with conservative treatment with respect to neurological outcome. 53 In that study, however, again the timing of surgery was not considered as a factor affecting outcome.…”
Section: Literature Reviewmentioning
confidence: 91%
See 1 more Smart Citation
“…The same conclusions were made by reviewing the outcome of conservative treatment of 50 consecutive patients with between 10% to 90% canal encroachment in Frankel C, D and E groups; patients in Frankel C and D group recovered ambulation and none of the patients deteriorated neurologically or otherwise [13] Other groups have since published similar findings [14][15][16].…”
Section: Canal Encroachmentmentioning
confidence: 72%
“…Boerger et al in July 2000 9 reviewed the literature and came to a similar conclusion stating that clearance of the spinal canal is not necessary for neurological recovery. Unfortunately, I cannot ®nd any convincing evidence in the literature to suggest that either the speed of recovery or the ®nal neurological outcome are improved by surgery (decompression+stabilisation) in patients with complete or incomplete cord injuries.…”
Section: Third Opinionmentioning
confidence: 87%